Analysis of Mathematical Creative Thinking Ability on Junior High School Students in Bandung - Hikmal Setiawan; Nelly Fitriani (IKIP Siliwangi, 2023)
This research is motivated by the importance of quadrilateral material in mathematics lessons, especially for students as an educational subject in everyday life, while the aim is to analyze students’ mathematical creative thinking abilities in solving quadrilateral problems. This research is a qualitative descriptive study. The population in this study were all seventh-grade junior high school students in the city of Bandung whose sample was randomly selected at Paulus Middle School as many as 32 people. Students can be classified based on their creative thinking abilities based on (1) the Ability creative thinking of students with the high category is fulfilling 3 indicators of creative thinking namely fluency, flexibility, and novelty, so students with the high category is said to be creative. (2) Students' ability to think creatively with the medium category is fulfilling 2 indicators of creative thinking, namely fluency and flexibility, so students in the medium category are said to be not creative. (3) The creative thinking ability of students in the low category is fulfilling 1 indicators of creative thinking are fluency and students in the moderate category said students who are not creative. Data is obtained by testing creative thinking test questions as many as 4 questions that contain indicators. The results showed that there were 2 people with high ability, 4 people with moderate ability, and 26 people with low ability with various errors including conceptual errors, principal errors, and data operation errors. Based on this, it can be concluded that the creative thinking skills of junior high school students are still relatively low.